Traits of poverty, work and disease in the life cycle of women - Juárez, María Paula (Horizonte Sanitario, 2019)
Objective: To find out how work, poverty, health, disease from childhood histories and adulthood enter into the life of a group of women in extreme poverty belonging to three communities in the Gran Río Cuarto region (Córdoba, Argentina), taken from their biographical accounts and from psycho-social and pedagogical research. Materials and methods: The study is carried out with a methodology of qualitative, interpretative and critical research. For the data collection interviews were used with women, the sample being formed from a criterion of voluntary participants. The process of qualitative data analysis was carried out from a diachronic perspective, proceeding through a narrative biographical approach that allowed to consider the temporal sequence in the stories of the interviewed, identifying key moments in the relationship between work, health, illness, childhood and adulthood. A categorical narrative analysis was carried out that enabled the dialogue between the different women´s narratives. Results: Eleven interviews were conducted with women between the ages of 22 and 66, from whose study two categories emerged based on their testimonies and narratives: 1. Childhood, work and illness, and 2. Adulthood, work and illness. The analysis of these categories shows how work enters the life of women early, as a requirement imposed in a childhood crossed by efforts, suffering, physical and psycho-emotional pain. The situation does not seem to improve with adulthood where work intensifies and along with it their conditions of precariousness, exposure to risks, fatigue, weakness of the body and the possibility of getting sick. Conclusions: The study tries to pay attention to a complex reality for the construction of transformation alternatives from a commitment to the design and execution of public and social policies, programs and projects in socio-health areas. Keywords: poverty; work; disease; woman.